PNI Organisasi Politik Sesudah 1926 - Naya Valentina (Program Studi Pendidikan Sejarah Universitas Riau, 2022)
This article was created to complete an Indonesian history coursework. In writing an article entitled “PNI Political Organizations After 1926”, this research was conducted using the historical or historical method, which is the method used to describe events that have occurred in the past. Which consists of heuristics, criticism, interpretation, and then historiography. The first historical research procedure is heuristics. This stage is the initial stage in processing, finding and collecting sources of information or documents needed and related to the problems discussed. As a result of the failure of the PKI in carrying out a rebellion against the Dutch colonial government in 1926/1927, many minds at that time felt the need for a new forum or place or organization to become a place or channel for the aspirations of the people. In 1926, about two years after Cokroaminoto published his writings